Pinning energy and anisotropy properties of a Fe(Se, Te) iron based superconductor. (1st April 2019) - Galluzzi, A; Buchkov, K; Nazarova, E; Tomov, V; Grimaldi, G; Leo, A; Pace, S; Polichetti, M
Abstract: The measurements of DC magnetization M as a function of magnetic field ( H ) and time ( t ) have been performed in order to study the superconducting and pinning properties of a Fe(Se, Te) iron based superconductor fabricated by means of the Bridgman technique. By performing the superconducting hysteresis loops M ( H ) at different temperatures in the case of perpendicular and parallel field, the critical current density Jc ( H ) has been extracted in the framework of the Bean critical state model for both configurations. The Jc ( H ) curves have shown the presence of the second magnetization peak effect that causes an anomalous increase in the field dependence of the critical current density. In order to obtain the Jc anisotropy of the sample, we have performed the ratio between perpendicular and parallel critical current density values J c H ∣ ∣ c / J c H ∣ ∣ a b and compared its values with the literature ones. The information regarding the pinning energy U have been extracted by means of the relaxation of the irreversible magnetization M ( t ) in the case H ∣∣ c . In particular, performing relaxation measurements at different temperatures and magnetic fields, the temperature dependence of the pinning energy U ( T ) at different magnetic fields has been obtained showing an anomalous temperature scaling of the curves. The presence of a maximum in the U ( T ) curves suggests a pinning crossover at a given field and temperature H cr ( T ). The H cr ( T ) values have been fitted with the equation H cr ( T ) =  H cr (0) (1 −  T / T *) n whose results confirm the correlation between the elastic/plastic crossover and the end of the peak effect phenomenon.